Pemetaan Potensi Energi Panas Bumi Pada Provinsi Sumatera Utara Berbasis Digital Melalui Quantum GIS - Agung Dwi Laksono; Ahmad Afif Setiawan Habibi; Deva Tri Febiana; Nida Ayu Magfiroh Bahri; Sa’adatun Nisa'; Siti Diah Ayu Febriani (Proklamasi 45 University, 2023)
The location of Indonesia, which is located between three major tectonic plates, has an advantage in the field of alternative energy, namely geothermal heat. This research was conducted in order to facilitate the government and the community in North Sumatra Province regarding the existing geothermal potential. Geothermal energy or can be called geothermal is heat energy contained in water fluid or in the form of steam, liquid, or a mixture of both which is at a depth of more than 1 kilometer below the earth's surface. Indonesia has a geothermal potential of 40% of the total geothermal potential in the world, Indonesia is in second place, which is 23.76 GigaWatt (GW). One example is in North Sumatra in the Sarulla (330 MW) and Sibayak (120 MW) and Dolok Marawa (38 MW) areas. This study aims to create a mapping of geothermal potential in the province of North Sumatra using Quantum GIS by conducting literature studies, data collection, data management, and map visualization on Quantum GIS. reduce the use of fossil energy that is not friendly to the environment. The results show that the largest Geothermal Working Capacity Area (WKP) in North Sumatera is in South Tepanuli Regency with a total of 1,046 MW in Sibual Buali WKP and the second highest is Mandailing Regency of 240 MW.